2011
DOI: 10.1007/s10641-011-9918-8
|View full text |Cite
|
Sign up to set email alerts
|

Starvation reduces the heat shock protein responses in white sturgeon larvae

Abstract: This study investigates the responses of white sturgeon larvae (Acipenser transmontanus) to starvation and thermal stress, through the measurement of nutritional status (i.e. growth performances) and cellular biomarkers: heat shock proteins (Hsp) 70 and 90. White sturgeon larvae (25 day post hatch; initial weight 179.0±5.1 mg) were fed (20% body weight per day) or starved for 24, 48 or 72 hrs. Every 24 hrs, five larvae from each of the starved or fed treatment replicates were exposed to heat shock resulting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 36 publications
(42 reference statements)
1
21
0
Order By: Relevance
“…Increased protein catabolism in response to food limitation is closely related to gluconeogenesis, the process to utilize gluconeogenic substrates such as amino acids to maintain circulating glucose levels (McCue, 2010). There have also been studies that have shown a positive correlation between increased Hsp70 levels and increased food availability (Deng et al, 2009;Han et al, 2012). The energy-dependence of the Hsp70 response can be attributable to increased protein synthesis, alterations in protein metabolism, and/or several ATP-dependent reactions that involve Hsp70-like proteins (Pelham, 1986) and therefore changes in food availability can affect how energy is allocated to protein homeostasis.…”
Section: Hsc/hsp70 Protein Levelsmentioning
confidence: 99%
“…Increased protein catabolism in response to food limitation is closely related to gluconeogenesis, the process to utilize gluconeogenic substrates such as amino acids to maintain circulating glucose levels (McCue, 2010). There have also been studies that have shown a positive correlation between increased Hsp70 levels and increased food availability (Deng et al, 2009;Han et al, 2012). The energy-dependence of the Hsp70 response can be attributable to increased protein synthesis, alterations in protein metabolism, and/or several ATP-dependent reactions that involve Hsp70-like proteins (Pelham, 1986) and therefore changes in food availability can affect how energy is allocated to protein homeostasis.…”
Section: Hsc/hsp70 Protein Levelsmentioning
confidence: 99%
“…Here, on the other hand, there was no effect of feed ration treatment on mucus or brain HSC/HSP70 protein levels at acclimation temperature (18°C) or most of the heat shock temperatures (24 to 28°C for brain and 24 to 26°C for mucus). Nutritional effects on the cellular HSP70 response to heat shock are better studied for the sympatric white sturgeon, as both starvation (Han et al 2012) and low ration (Deng et al 2009) were shown to reduce the HSP70 protein response in larval white sturgeon.…”
Section: High Temperature Tolerancementioning
confidence: 99%
“…Other sturgeon species have been shown to successfully adjust their diet to altered prey availability (Brosse et al 2000;Usvyatsov et al 2012), and the Asian overbite clam has been identified as a major component of the diet of the sympatric white sturgeon (Kogut 2008). However, in sturgeons, manipulation of diet ration or nutritional content has been shown to affect growth, energetic status (Hung and Lutes 1987;Cui et al 1997;Hung et al 1997;Deng et al 2009;Han et al 2012;Haller et al 2015) and the cellular response to heat stress (Deng et al 2009;Han et al 2012;Wang et al 2013). Furthermore, diet composition and nutritional status have been shown to influence swimming capacity (Wagner et al 2004;Chatelier et al 2006;Wilson et al 2007;Gingerich et al 2010;Pettersson et al 2010;Killen et al 2014;Silva et al 2014), osmoregulation (Kirschner 1995;Tseng and Hwang 2008;Haller et al 2015), growth at high temperatures (Glencross and Rutherford 2010;Zhou et al 2013) and tolerance of high temperatures (Akhtar et al 2011;Kumar et al 2014;Patterson and Green 2014;Tejpal et al 2014) for a wide range of fish species.…”
Section: Introductionmentioning
confidence: 99%
“…The same trend was found in the literature with various sturgeon species and tissues (see Table 2 for details on species, tissues and HSP). HSP protein levels increase as a consequence of heat stress (Allen et al 2006;Deng et al 2009;Han et al 2012;LinaresCasenave et al 2013;Silvestre et al 2010;Wang et al 2013;Werner et al 2007;Zheng et al 2015), acute cold stress, air exposure (Wang et al 2013), and contamination (Keyvanshokooh et al 2009), but not during salinity acclimation (Sardella and Kültz 2009). Hsp mRNA expression increases with high stocking density or after an acute hypoxic stress (Ni et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained by a lower metabolic rate due ; gastrointestinal tract (GIT) to the lack of nutrients or starvation (Han et al 2012). In rainbow trout (Oncorhynchus mykiss), supplementation with selenomethionine reduces the negative performance impact of overcrowding but decreases hsp70 expression in muscle compared to the basal expression level and stress expression level in diet controls (Küçükbay et al 2009).…”
Section: Discussionmentioning
confidence: 99%